Cost analysis of MOUD implementation and sustainability in Massachusetts jails - Danielle Ryan; Don Lochana Ekanayake; Elizabeth Evans; Edmond Hayes; Thomas Senst; Peter D. Friedmann; Kathryn E. McCollister; Sean M. Murphy (Health & Justice)
Abstract Background In 2018 Massachusetts mandated that county jails offer all FDA-approved medications for opioid use disorder (MOUD) to incarcerated individuals with OUD. Estimating costs needed to implement and sustain an MOUD program are not clearly known in jail facilities. The objective of this study was to identify the type of MOUD model deployed by the jails serving as research sites for the Massachusetts JCOIN hub, determine which resources were utilized at each stage of development, and estimate the associated costs. Methods Resources required to implement and sustain the MOUD programs were identified through detailed, site-specific microcosting analyses at six participating jails in Massachusetts. Quantitative resource utilization data were captured primarily through in-person site-visits and semi-structured interviews with key personnel. Unit costs were derived from the Federal Supply Schedule and Bureau Labor of Statistics from a site-specific level perspective. Our customizable budget impact tool, designed to assist jails/prisons with assessing the viability of alternative MOUD models, was used to organize each site’s resources and estimate their associated costs. Resources/costs were summarized by site, according to type and phase, and cross-site comparisons were made to identify common program elements and unique models. Results Three MOUD models were identified. Model 1 consisted of a vendor hired to deliver and administer methadone daily, while clinical jail staff administered buprenorphine and extended-release naltrexone. Model 2 included facilities that hired a certified vendor to operate an in-house opioid treatment program (OTP) to oversee the administration of all MOUD. Jails in Model 3 became certified OTPs, thereby allowing jail staff to manage all aspects of the MOUD program. There was considerable variability in implementation costs, both within and across models, driven by model-specific factors, but also with switching models, expanding infrastructure, etc. Entering the sustainment phase, the per-person costs of care were quite similar across models but differed according to the proportion of costs considered time-dependent vs. variable. Conclusion Our findings represent the most detailed and comprehensive estimates of resource/cost requirements for jail-based MOUD programs. Given the budget constraints faced by jails, the investment required to implement/sustain an MOUD program will likely result in the need to obtain additional funding or reallocate existing resources away from other initiatives.